2022
DOI: 10.3390/life13010061
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Morphological, Physiological, and Phytochemical Responses in Centella asiatica L. Urban to Incremental Salinity Stress

Abstract: Centella asiatica L. as a traditional medicinal plant is popular in several Asian countries and characterized by the presence of phytochemicals, such as phenolics and flavonoids. Soil salinity can affect the growth and phytochemical composition in this plant species. In this study, the effects of incremental soil salinity (0, 25, 50, 75, and 100 mM NaCl) on growth, physiological characteristics, total phenolic and total flavonoid contents, including the antioxidant activity of Centella asiatica L., were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…The increase in total chlorophyll content was due to the increase in nitrogen content in the fertilization treatments. Previous studies have shown a close relationship between chlorophyll content and nitrogen content in fertilizers (Hoang et al 2023). Nitrogen is a factor in chlorophyll biosynthesis because the chlorophyll molecule contains nitrogen.…”
Section: Total Chlorophyll Contentmentioning
confidence: 95%
“…The increase in total chlorophyll content was due to the increase in nitrogen content in the fertilization treatments. Previous studies have shown a close relationship between chlorophyll content and nitrogen content in fertilizers (Hoang et al 2023). Nitrogen is a factor in chlorophyll biosynthesis because the chlorophyll molecule contains nitrogen.…”
Section: Total Chlorophyll Contentmentioning
confidence: 95%